2021
DOI: 10.1126/sciadv.abd3176
|View full text |Cite
|
Sign up to set email alerts
|

Plant rhizodeposition: A key factor for soil organic matter formation in stable fractions

Abstract: Soil organic carbon formation remains poorly understood despite its importance for human livelihoods. Uncertainties remain for the relative contributions of aboveground, root, and rhizodeposition inputs to particulate (POC) and mineral-associated (MAOC) organic carbon fractions. Combining a novel framework with isotope tracer studies, we quantified POC and MAOC formation efficiencies (% of C-inputs incorporated into each fraction). We found that rhizodeposition inputs have the highest MAOC formation efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
109
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 217 publications
(115 citation statements)
references
References 76 publications
4
109
0
2
Order By: Relevance
“…Soil biodiversity is linked to soil organic matter (SOM), which composition, and origin are a matter of debate and ongoing studies (2,3). It is accepted that both microbial necromass (4) and plant rhizo-deposition (5) are critical factors in SOM build-up and C sequestration. Both microbial necromass and microbial-derived compounds explain soil mineral-associated (MAOM) and particulate (POM) organic matter aggregation as a result of microbial activity (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil biodiversity is linked to soil organic matter (SOM), which composition, and origin are a matter of debate and ongoing studies (2,3). It is accepted that both microbial necromass (4) and plant rhizo-deposition (5) are critical factors in SOM build-up and C sequestration. Both microbial necromass and microbial-derived compounds explain soil mineral-associated (MAOM) and particulate (POM) organic matter aggregation as a result of microbial activity (5).…”
Section: Introductionmentioning
confidence: 99%
“…It is accepted that both microbial necromass (4) and plant rhizo-deposition (5) are critical factors in SOM build-up and C sequestration. Both microbial necromass and microbial-derived compounds explain soil mineral-associated (MAOM) and particulate (POM) organic matter aggregation as a result of microbial activity (5). Soil organic matter (SOM) changes and losses have commonly been associated with soil cultivation, especially conventional agriculture practices (6).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, considering that biodiversity loss is a major driver of reduced multifunctionality across all terrestrial ecosystems (Cardinale et al, 2012;Fanin et al, 2018), biodiversity-based, resilience-oriented farming practices must be targeted if the aim is to restore landscape multifunctionality (Foley et al, 2005(Foley et al, , 2011Kremen and Merenlender, 2018). Alternatives for the re-diversification of agricultural systems with associated gains in ES delivery include the use of diversified crop rotations or polycultures (Kremen and Merenlender, 2018;Bowles et al, 2020;Guzman et al, 2021), cover crops (Pinto et al, 2017;Sekaran et al, 2021;Villarino et al, 2021) and the recoupling of crop and livestock production (Soussana and Lemaire, 2014;Sekaran et al, 2021).…”
Section: Restoring Landscape Multifunctionality: Planned Biodiversity Reconnecting Grazing Animals To Crop Landscapesmentioning
confidence: 99%
“…Soil carbon is often considered in terms of distinct soil organic matter "pools": either associated with minerals, occluded within microaggregates, or "free" (not subject to either chemical or physical protection) (Poeplau et al, 2018). Recent studies have shown that labile carbon substrates can play an important role in SOM formation and stabilization in both physically (occluded) and chemically (mineral-associated) pools (Cotrufo et al, 2015;Totsche et al, 2017;Villarino et al, 2021), while plant litter is generally understood to largely comprise the free-light fraction material. The mineral-associated or "heavy fraction" is of particular interest for soil organic carbon persistence; it is typically the oldest distinct pool (Torn et al, 1997) and represents carbon stabilized via mineral sorption and co-precipitation mechanisms (Kogel-Knabner et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The mineral-associated or "heavy fraction" is of particular interest for soil organic carbon persistence; it is typically the oldest distinct pool (Torn et al, 1997) and represents carbon stabilized via mineral sorption and co-precipitation mechanisms (Kogel-Knabner et al, 2008). This fraction of SOM, commonly termed MAOM (mineral-associated organic matter) (Cotrufo et al, 2019), is largely of microbial origin and thought to be derived from relatively labile C substrates (Clemente et al, 2011;Cotrufo et al, 2013;Villarino et al, 2021). Recent work has suggested that microbial necromass may be a primary precursor to stable organic matter in grasslands (Angst et al, 2021).…”
Section: Introductionmentioning
confidence: 99%